1940
DOI: 10.1084/jem.72.4.389
|View full text |Cite
|
Sign up to set email alerts
|

A Soluble Antigen of Lymphocytic Choriomeningitis

Abstract: Anti-soluble substance antibodies and neutralizing substances, which develop following infection with the virus of lymphocytic choriomeningitis, appear to be separate entities. The times of appearance and regression of the two antibodies are different in both man and the guinea pig; the antisoluble substance antibodies appear earlier and remain a shorter time. Moreover, mice develop them but no demonstrable neutralizing substances. Injection of formalin-treated, virus-free extracts containing co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

1943
1943
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…MATERIALS (28) for demonstrating fixation with choriomeningitis materials, a modification of the procedure described for the psittacosis test was adopted in order to simplify the work. The two methods gave equally satisfactory results with choriomeningitis, but the former was less desirable for psittacosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…MATERIALS (28) for demonstrating fixation with choriomeningitis materials, a modification of the procedure described for the psittacosis test was adopted in order to simplify the work. The two methods gave equally satisfactory results with choriomeningitis, but the former was less desirable for psittacosis.…”
mentioning
confidence: 99%
“…Samples of serum from each patient were titered for antibodies against the soluble antigen of choriomeningitis over the range of dilutions from 1: 2 to 1: 32. Previous work had demonstrated that these immune substances are detectable in human sera during only a few weeks in convalescence, i.e., usually between the third and sixth weeks (28). Therefore, results were recorded as negative only for those patients whose sera taken during this period failed to fix complement in the presence of soluble antigen.…”
mentioning
confidence: 99%
“…It becomes detectable around the eighth day and soon reaches moderate titres of 64 to 128 as is shown in Fig. 7 (Traub and Schafer, 1939;Smadel and Wall, 1940;Weigand and Hotchin, 1961;Volkert, Larsen, and Pfau, 1964;Larsen, 1968;1969b;Lewis and Clayton, 1969). By way of contrast, neutralizing antibody does not appear till the fourth week after infection, and the titres increase slowly reaching maximum values between 50 and 100 days (Fig.…”
mentioning
confidence: 83%
“…Some of them are refractory to disease [14,86,137,138,139,140,141,142,143,144]. Arenaviruses co-evolved with their natural host but little is known about those processes in other animals and the implication for pathogenesis.…”
Section: Arenavirus Plasticitymentioning
confidence: 99%